2010
DOI: 10.1097/bsd.0b013e318193c16c
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes After Microendoscopic Discectomy for Recurrent Lumbar Disc Herniation

Abstract: MED is a safe and effective surgical approach for the treatment of recurrent lumbar disc herniation. Standardized measures of outcome show that MED for recurrent herniation produces improvement in pain, disability, and functional health that is at least comparable with outcomes reported for conventional open microdiscectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
41
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 22 publications
2
41
1
1
Order By: Relevance
“…33 The overall success rate of 90% in our series is comparable to reported success rates of MED and ETD in the literature. 1,7,14,15,24,25,32,39,43 The mean operative time of 90 ± 35 minutes is comparable to other series using MED (98-102 minutes). 15,24,25 The instability/fusion rate in our series was 6.7%.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…33 The overall success rate of 90% in our series is comparable to reported success rates of MED and ETD in the literature. 1,7,14,15,24,25,32,39,43 The mean operative time of 90 ± 35 minutes is comparable to other series using MED (98-102 minutes). 15,24,25 The instability/fusion rate in our series was 6.7%.…”
Section: Discussionsupporting
confidence: 67%
“…15,24,25 The instability/fusion rate in our series was 6.7%. In another series of 16 patients 43 and in two 10-patient series described by Le et al 24 and Isaacs et al 15 in 2003, no case of instability and fusion was reported. In our series, we report an incidental durotomy rate of 16.7%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 In cases of revision surgery, it is important to remove additional bone superior to the previous laminotomy to access normal dura, and then follow that plane into the scarred area.…”
Section: Discussionmentioning
confidence: 99%